P1 finite element methods for an elliptic optimal control problem with pointwise state constraints. (19th November 2018) - Brenner, Susanne C; Sung, Li-yeng; Gedicke, Joscha
Abstract: We present theoretical and numerical results for two $P_1$ finite element methods for an elliptic distributed optimal control problem on general polygonal/polyhedral domains with pointwise state constraints.